Experimental poisoning by the leaves of Ricinus communis in cattle - Tokarnia, Carlos Hubinger; Döbereiner, Jürgen; Canella, Camillo F.C. (Pesquisa Agropecuaria Brasileira, 2014)
The leaves of Ricinus communis L. are said, particularly in northeastern Brazil, to be toxic to cattle. References in the literature to the toxicity of the leaves of this plant are scarce, vague and contradictory. Fresh green leaves and, in a few experiments, the dried leaves of R. communis, collected in the State of Rio de Janeiro, were given orally to 25 bovines in different amounts and at different periods of the year, and in some animals the doses were repeated. The experiments were made with leaves with whitish and with violet stems. Additionally a series of experiments was performed in 12 bovines in the State of Ceará, northeastern Brazil, with the fresh green and with the wilted sun-warm leaves, left in the sun for one hour; in both cases the stems were whitish. There was no difference in the toxicity of the leaves with whitish and with violet stems, between the leaves from the State of Rio de Janeiro and those from the State of Ceará, as also not between the fresh green and the wilted sun-warm leaves. The dosis of 20 g/kg of the leaves caused death in 8 of 12 bovines; doses from 10 to 12.9 g/kg given to 11 bovines, caused the death of only one of them, one which had received 10 g/kg. The plant had no cumulative effect. Probably there is the development of a small tolerance. The dried leaves collected up to 19 weeks before experimentation and kept at room temperature, lost approximately half of its toxicity. The clinical signs, caused by ingestion of the leaves of R. communis, those from the State of Rio de Janeiro as well as those from Ceará, the fresh green, the wilted sun-warm leaves, and the dried leaves, were always the same and were mainly neuro-muscular in nature; swaying gait, necessity to lie down after short periods of exercise, difficulties in lying down, muscular tremors, salivation, chewing movements, excessive eructation, and recovery in a short period or death. The first signs appeared between 3 and 6 hours after ingestion of the leaves. When the animals survived, the signs lasted between 2 and 10 hours. Recovery was complete within 13 hours, at the most. When the animals died, the signs lasted between 2 and 15 hours, and death occurred from 5 to 20 hours after having eaten the leaves. The post-mortem findings were negative and the histopathologic examinations revealed slight to severe hydropic degeneration in the liver. The clinical picture observed in these experiments indicates that the toxic principle of the leaves of R. communis is not ricin which is responsible for the toxicity of the seed. The leaves cause neuro-muscular signs, whereas the seeds cause gastro-intestinal disorders.